Photoinitiating characteristic of erythrosine B derivatives and its application on pigmented visible photo-curing ink of textile digital printing. Issue 20 (December 2016) - Nan, Xuying; Sun, Guangdong; Huang, Yi; Fan, Qinguo; Yao, Yuhua; Shao, Jianzhong
Eight visible photoinitiators composed of a series of erythrosine B derivatives with different structures, combined with ethyl-4-dimethylaminobenzoate and diphenyliodonium hexafluorophosphate, were evaluated for their photoinitiating characteristic and the tensile properties of photo-curing films initiated by them, to acquire the relationship between structure and performance. The visible photoinitiator was the key component for the pigmented visible photo-curing ink of textile digital printing. So, based on the experimental results, the preferred photoinitiator was incorporated into three pigmented photo-curing inks (red, yellow and blue) to perform textile digital jet printing. After photo-curing under visible light irradiation, the printed fabric samples showed excellent dry–wet rubbing fastness, and possessed a consistent hue with the samples initiated by the photoinitiator containing camphorquinone.